Compassionate Design: Utilizing Design Thinking to Preserve Sanctity, Dignity, and Personhood When Children Die. Issue 4 (July 2020) - Grossoehme, Daniel H.; Mark, Melissa S.; Lane, Blake; Rednour, Allison; Thienprayoon, Rachel
Abstract : Introduction: Greater than 70% of children who die in our institution annually die in an intensive care unit (ICU) setting. Family privacy, visitation policies, and an inability to perform religious rituals in the ICU are barriers to provide children with culturally competent, family-centered care when a child dies. The goal of this project was to profoundly understand family and staff experiences surrounding pediatric death in our institution to identify unique opportunities to design improved, novel delivery models of pediatric end of life (EOL) care. Methods: This project utilized a structured process model based on the Vogel and Cagan's 4-phase integrated new product development process model. The 4 phases are identifying, understanding, conceptualizing, and realizing. We utilized an adaptation of this process model that relies on human-centered and design thinking methodologies in 3 phases: research, ideation, and refinement of a process or product opportunity. Results: There were 2 primary results of this project: 5 process and opportunity areas to improve the EOL experience across the hospital, and a set of criteria and considerations for a dedicated EOL space. Discussion: Sometimes, the best outcome we can provide for a child and their family is a peaceful, dignified death. This project utilized human-centered design to create improved process outcomes and to design a dedicated EOL space for children who die in the hospital. Offering grieving families quiet, private time with their child in a beautiful, dignified, peaceful location enables the beginning of improved bereavement outcomes for the family and staff. Abstract : Supplemental Digital Content is available in the text.